KISAH DAN DAKWAH MENURUT ALQURAN (SUATU PENDEKATAN KEBAHASAAN) - Hasan, M. (Hunafa: Jurnal Studia Islamika, 2005)
In the Holy Qur’an there are several narratives that tell past events along with their actors and their places such as the narrative of prophets, past events that can occur again in the future such as the narrative on the killing of Habil by Qabil, or symbolic narrative describing no event but can occur in the future. The main objective of the expression of narrative in the Holy Qur’an is to spread Islamic mission. This can be seen from Qura’nic instruction to people to observe the creation of the universe, past events and questions asked, all of which order them to think of themselves and  their surroundings. Kata kunci : Alquran, kisah, dakwah